Traditional Chinese Medicine Shi-Bi-Man regulates lactic acid metabolism and drives hair follicle stem cell activation to promote hair regeneration - Haojie Du; Tao Zhang; Qiao Wang; Xinran Cao; Huiwen Zheng; Jiabin Li; Jianxia Zhu; Jiao Qu; Lehang Guo; Yang Sun (BMC, 2023)
Abstract Background As a supplement for promoting hair health, Shi-Bi-Man (SBM) is a prescription comprising various traditional Chinese medicines. Though SBM has been reported to promote hair regeneration, its molecular mechanism remains unclear. Cynomolgus monkeys (Macaca fascicularis) are non-human primates with a gene expression profile similar to that of humans. The purpose of this research is to evaluate the effect of SBM on promoting hair regeneration in cynomolgus monkeys and to reveal the underlying mechanism. Methods The effect of SBM on hair regeneration was observed by skin administration on 6 cynomolgus monkeys with artificial back shaving. The molecular mechanism of SBM was studied using single-cell RNA sequencing (scRNA-seq) in combination with quantitative polymerase chain reaction (qPCR) detection for gene transcription level, and immunofluorescence staining verification for protein level. Results SBM significantly induced hair regeneration in cynomolgus monkeys, increased hair follicle number and facilitated hair follicle development. ScRNA-seq revealed an increase in the number of hair follicle stem cells (HFSCs) with a higher activation state, as evidenced by the higher expression of activation marker LDHA related to metabolism and the proliferation marker MKI67. Immunofluorescence analysis at the protein level and qPCR at the mRNA level confirmed the sequencing data. Cellchat analysis revealed an enrichment of ligand-receptor pairs involved in intercellular communication in Laminin-related pathways. Conclusion SBM significantly promotes hair regeneration in cynomolgus monkeys. Mechanically, SBM can up-regulate LDHA-mediated lactic acid metabolism and drive HFSC activation, which in turn promotes the proliferation and differentiation of HFSCs.